Enhancing Tumor Immunity with IL-12 and PD-1 Blockade: A Strategy for Inducing Robust Central Memory T Cell Responses in Resistant Cancer Model - Fentian Chen; Kexin Wu; Shiqi Lin; Jinlong Cui; Xiaoqing Chen; Zhiren Zeng; Na Yuan; Mujin Fang; Xue Liu; Yuanzhi Chen; Wenxin Luo (Antibodies)
Background: Although immune checkpoint inhibitors (ICIs) have demonstrated efficacy in treating advanced cancers, their therapeutic success remains limited for many patients, with initial responders often experiencing resistance and relapse. Interleukin-12 (IL-12) is a powerful cytokine for antitumor immunotherapy, enhancing both lymphocyte recruitment into tumors and immune cell activation. Methods: In this study, we successfully produced mouse interleukin-12 (mIL12) through eukaryotic recombinant expression. In vivo, mIL12 exhibited significant control of tumor immunity in ICI-resistant and aggressive tumor models. Further mechanistic analysis indicated that treatment with mIL12 led to a substantial increase in tumor-infiltrating CD4+ T, CD8+ T, cDC1, and CD103+ cDC1 cells. Results: Our data underscore the potential of a combined therapeutic strategy involving IL-12 with PD-1 and CTLA-4 blockade to elicit a potent antitumor immune response. Notably, the co-administration of mIL12 and PD-1 blockade significantly enhanced the presence of central memory T cells (TCM) within tumors. Conclusions: This study is the first to provide evidence that the combination of mIL12 and PD-1 blockers promotes the generation of TCM, potentially contributing to a robust and durable antitumor effect.